A novel device for delivery of intranasal particulate medication: a pilot study. Issue 11 (18th July 2013) - Khalili, Sammy; Tkachenko, Natalia; Rotenberg, Brian
<x xml:space="preserve">Abstract</x> Background Intranasal medication delivery for allergic rhinitis (AR) is considered a mainstay of therapy but is hampered by poor compliance. Among reasons given are unpleasant sensations associated with spray penetration into the pharynx. Our objective was to study a novel method of particle delivery to the nose that would abrogate these issues. Methods This was a double‐blind, randomized study. Subjects who met study criteria underwent intranasal particle delivery using a novel device (Trivair Nasal Deposition System; Trimel Pharmaceuticals, Toronto, Canada) that delivered anhydrous lactose particles into the nose via a transoral air puff (thus elevating soft palate and blocking the nasopharynx). Subjects had nostrils randomized into 4 groups (particle sizes 5 μm and 50 μm × doses 12.5 mg and 25 mg). Particle deposition was assessed at 1 minute, 10 minutes, and 30 minutes on the inferior turbinate, middle turbinate, and nasopharynx, respectively, using high‐definition endoscopic photography. Each image was compared using an expert blinded 2‐person panel for percentage particles remaining. Nonparametric data was assessed using the Wilcoxon signed‐rank test via Strata software. Results Twelve nostrils in total met study criteria. The results showed no difference in effectiveness of nasal particle retention between the groups based on particle size or dose. No particles entered the nasopharynx or oropharynx. Conclusion This study provides proof‐of‐principle data that the Trivair Nasal Deposition System is effective at retaining medication in the nose without pharyngeal penetration. Larger studies on this device are warranted.